2013
DOI: 10.3109/00207454.2012.763164
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydrocephalus on the periventricular white matter in intracerebral hemorrhage: a diffuser tensor imaging study

Abstract: The anterior corona radiata was found to be more compressed by hydrocephalus than the other five regions of periventricular white matter examined in patients with hydrocephalus following ICH. It is believed that the results of the present study will be useful for the diagnosis and management of hydrocephalus following stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
0
29
1
Order By: Relevance
“…The FA value is closely related to the myelin integrity, nerve fiber density, and orientation. [10,23,24] In this study, we found that the FA values of ROIs before the ventriculoperitoneal shunt were substantially lower in the patients than the control group, which might reflect the demyelination of the white matter caused by enlarged ventricles and high intracranial pressure. [25,26] The FA values significantly increased in the patients after surgery, which might be due to the reduced intracranial pressure, improved CSF circulation, and restored myelination.…”
Section: Discussionmentioning
confidence: 83%
“…The FA value is closely related to the myelin integrity, nerve fiber density, and orientation. [10,23,24] In this study, we found that the FA values of ROIs before the ventriculoperitoneal shunt were substantially lower in the patients than the control group, which might reflect the demyelination of the white matter caused by enlarged ventricles and high intracranial pressure. [25,26] The FA values significantly increased in the patients after surgery, which might be due to the reduced intracranial pressure, improved CSF circulation, and restored myelination.…”
Section: Discussionmentioning
confidence: 83%
“…43 Cross-sectional studies have shown that DTI parameters can differentiate brain structures with hydrocephalus from normal controls in both human and animal studies. 16,22,27,30,34,38,4042,44 Initial longitudinal studies have shown that DTI parameters had variable degrees of tendency to return to a normal range after surgery. 2,6,26,36 However, there is also strong evidence from both clinical and experimental studies suggesting that the damage to brain structures suffered before CSF diversion may be irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is difficult to determine whether damage occurs prior to or during treatment of hydrocephalus. Diffusion tensor imaging (DTI), a modality of magnetic resonance (MR) imaging, has emerged as a very useful tool in assessing structural changes within the body, especially within the white matter of the brain [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In this experimental study, we investigated DTI changes in various white matter structures known to be damaged in hydrocephalus to determine whether this modality could identify where and when damage is occurring during infantile hydrocephalus [2,3,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%